Neuroethics of sport : neuroenhancement - Erhardt, Julija (Array, 2020)
In the pursuit of perfection in a sport arena, with the help of sport science and its accompanying technologies, humans have been pushing up against the limits of their physical body. However, the limits of the human mind have not yet been fully explored. Although a vast majority of sports have a strong component of physical strength and skillfulness, they are tightly interwoven with perceptual and cognitive processes. The perfect performance requires the “perfect brain” and in the quest for excellence athletes are reaching for different means of neuroenhancement. Some of used enhancement methods are subject to doping control, but some of them are (still) out of regulatory boundaries. By integrating neuroscientific knowledge with ethical and social thought, the article will analyze different neuroenhancement approaches of these enhancement methods and related ethical issues.